Self-efficacy and motivation predict leisure time physical activity: a cross sectional study from India - Garg, Shalini (Journal of Interdisciplinary Lifestyle Studies, 2022)
Correlates of physical activity are relatively less understood in India. This study was conducted in the state of Kerala which suffers from a high burden of chronic diseases in the country due to epidemiological transition. A cross-sectional survey was conducted among 500 adults in Kottayam district of Kerala. Multivariable logistic regression analysis determined that high fitness motives (OR=8.45, 95%CI 1.58-11.34), high self-efficacy (OR=3.71, 95%CI 1.75-8.08), support from friends and family (OR=4.46, 95%CI 1.09-18.20) and being married (OR=2.59,95%CI 1.08-6.23) were key predictors of leisure time physical activity than their counterparts.